2단계 발효로 제조된 고산도 사과식초의 품질지표성분 설정 - 조윤희(Yunhee Jo); 박윤지(Yunji Park); 이현규(Hyun-Gyu Lee); 이혜진(Hye-Jin Lee); 정용진(Yong-Jin Jeong); 여수환(Soo-Hwan Yeo); 권중호(Joong-Ho Kwon) (한국식품과학회지, 2015)
In this study, high-acidity cider vinegar (HACV) was produced by alcoholic and acetic acid fermentation of apple concentrate without any nutrients and then the optimum alcohol concentration was determined through a qualitative study. HACV was fermented with different initial alcohol concentrations (6-9%) during the process of acetic acid fermentation. The highest content of reducing sugar, organic acids, and free amino acids was observed at 6% of initial alcohol concentration. Approximately 20 types of volatile compounds were identified by solid-phase microextraction (SPME) and GC-MS. The total volatile content was the highest at 6% of initial alcohol concentration, and the acid content was the lowest at 9% of the initial alcohol concentration. The HACV produced by a two-stage fermentation process was qualitatively better than commercial HACV presenting the highest value at 6% of initial alcohol concentration. Malic acid, aspartic acid, and hexyl acetate were selected as quality index components of HACV production by two-stage fermentation on the basis of correlation between their physicochemical properties and the sensory attributes of HACV.